Schriften zum Islam und zur arabischen Literatur der Gegenwart - Wielandt, Rotraud (Islamkundliche Untersuchungen, 2025)
Rotraud Wielandt produced her studies on modern Arabic literature and contemporary Islamic exegesis and theology during forty years of research. Although the texts contain important insights and original observations, some of them had appeared in remote venues. These works needed to be made accessible to contemporary Arabic and Islamic studies, and they are now available in a carefully revised edition